Analysis of Earthquake Risk Estimation for Sustainable Development Using Microtremor Data Based on Vs30 Distribution: Comparative Study of DFA and Geopsy in Central Bengkulu, Indonesia - Arya Putra Anggi; Refrizon, Refrizon; Harlianto, Budi; Apriyanti, Nurul; Saputri, Winda; Febriansyah, Gian Ori; Al-Ansory, Andre Rahmat; Raihana, Hana; Daniel, Adrian; Gumanty, Usman (Jurnal Ilmu Fisika, 2025)
This research was conducted in Pondok Kelapa Subdistrict, Central Bengkulu Regency, to analyze subsurface characteristics using microtremor data and the Horizontal-to-Vertical Spectral Ratio (HVSR) method. The research compared DFA (Diffuse Field Assumption) and Geopsy approach. In this study, 40 points were measured with a distance between points ranging from 200 to 300 meters. The data were processed using Terraware-HV and Geopsy software with a Monte Carlo approach to model the 3D subsurface structure. Results show that the dominant frequencies range from 0.64 to 8.19 Hz, with high amplification zones between 1.92 and 7.72 concentrated in areas of loose soil, indicating their high seismic susceptibility. Vs30 values range from 55 to 465 m/s, reflecting the dominance of soft to medium materials, such as clay, gravel, sand, and soft rock at specific depths. 3D modeling revealed a heterogeneous distribution of subsurface materials, with high amplification zones requiring special mitigation. This study provides important insights for seismic risk zoning, disaster mitigation, and earthquake-resistant structure design, and supports sustainable development planning in earthquake-prone areas. The results are expected to serve as a reference in spatial management based on earthquake risk mitigation.